Support of the Sharing Economy in France and Germany. - Osnabrügge, Johanna (Jihočeská univerzita, 2023)
The Sharing Economy represents a rapidly growing sector in the global economy, with companies such as Foodsharing and Blablacar becoming household names from Germany and France. This growth has been driven by entrepreneurs who have seen opportunities to leverage technology to create value for customers, while also transforming traditional business models. However, despite the potential of these companies to drive sustainable consumption and reduce waste, they face significant challenges in terms of regulation, funding, and support infrastructure. This master thesis aims to explore the support available to founders of Sharing Economy companies in France and Germany. This thesis will examine the regulatory frameworks, funding opportunities, support instances, and challenges that impact the founding process of Sharing Economy startups.
Keywords: sharing economy; francogerman; social entrepreneurship; green economy; european entrepreneurship